Legal Analysis of Responsibility for the Criminal Act of Aggravated Theft - Syahrul Ramadhan, La Ode Muhammad; Ma'ruf, Umar (Jurnal Hukum Khaira Ummah, 2025)
This thesis examines the application of criminal law to perpetrators of aggravated theft, with a specific focus on the juridical analysis of Decision Number 644/Pid.B/2024/PN Mtr. The research is motivated by the importance of fair and proportional law enforcement in cases of aggravated theft, particularly in determining criminal sanctions that align with the degree of culpability and the defendant's personal circumstances. The objective of this study is to analyze how the law is applied in sentencing the defendant and to assess the legal reasoning employed by the judge in delivering the verdict. This research adopts a normative juridical approach, emphasizing library research and analysis of relevant statutory provisions, legal doctrines, and judicial decisions. Primary data consists of the court ruling, while secondary data is obtained from legal literature related to substantive criminal law and criminal procedure. The findings of the study indicate that the legal application in this aggravated theft case refers to Article 363 of the Indonesian Criminal Code (KUHP). However, there is a discourse surrounding the proportionality of the sentence imposed. The judge considered several factors, including the socio-economic condition of the defendant, the defendant's confession and remorse, and the impact of the act on the victim. These considerations reflect the application of the principle of individualized sentencing, in which punishment is not solely retributive but also incorporates rehabilitative elements.